Mirrors of Entrapment and Emancipation - Babak Elahi (International Institute of Islamic Thought, 2016)
In 1992, Farzaneh Milani’s groundbreaking Veils and Words brought into dialogue the fields of Iranian studies and feminist critical theory – two areas of humanist inquiry that, in some sense, need each other. Moreover, with works like Hamid Naficy’s The Making of Exile Cultures (1993), interdisciplinary critical theory has informed many humanist and social science approaches to Iranian literature and culture. These links between integrated critical theory and Iranian studies can produce compelling and insightful analyses. However, the cadence of such work might be more in tune with one subfield than another. While the content and subject of these studies might include Iranian society, culture, or art, it is often the case that the critical method being deployed is more important than the historical, literary, or social content to which it is applied. Methodology eclipses the subject of analysis. This is the case with Leila Rahimi Bahmany’s Mirrors of Entrapment and Emancipation (Mirrors). Bahmany’s work tells us more about the feminist critical genealogy brought to bear on the work of Sylvia Plath (d. 1963) and Forrough Farrokhzad (d. 1967) than it does about the works and lives of these poets themselves. But if, as I note above, these fields do “need” each other, then this book is worth exploring for both feminist scholars and Iranian studies specialists. Beyond specialists, however, the work does little to draw in a reader not already at least slightly familiar with debates in psychoanalytic feminist theory of the twentieth century. Bahmany begins her book with the highly suggestive images of Narcissus and Echo from Ovid’s Metamorphoses. However, she quickly moves from this basis in classical western mythology to the relevance of these images for psychoanalysis and feminism. Thus, she rapidly establishes a ...